A Sensor Based on Hollow, Octahedral, Cu2O‐Supported Palladium Nanoparticles – Prepared by a Galvanic Replacement Reaction – and Carboxylic Multi‐Walled Carbon Nanotubes for Electrochemical Detection of Caffeic Acid in Red Wine. Issue 14 (10th April 2019) - Hu, Bibo; Zhang, Min; Liu, Peng; Xie, Shilei; Xie, Dong; Wang, Shoushan; Cheng, Faliang; Wang, Lishi
Abstract: A novel nanocomposites prepared from hollow, octahedral cuprous oxide supported palladium nanoparticles (Cu2 O‐PdNPs) through a facile galvanic replacement reaction and carboxylic multi‐walled carbon nanotubes (MWCNTs‐COOH) was modified on the surface of glassy carbon electrode (Cu2 O‐PdNPs@MWCNTs‐COOH/GCE) to fabricate a sensor for electrochemical detection of caffeic acid. The synergistic effect between Cu2 O‐PdNPs and MWCNTs‐COOH exhibited remarkable electrocatalytic activity, higher selectivity and higher sensitivity toward caffeic acid. At optimized test conditions, the Cu2 O‐PdNPs@MWCNTs‐COOH/GCE nanocomposites sensor revealed wider linear range of 0.006‐60 μM with a lower detection limit of 0.002 μM (S/N=3) for caffeic acid determination. Eventually, the proposed nanocomposites sensor was successfully applied to determine the concentration of caffeic acid in red wine samples. Abstract : A novel nanocomposites sensor prepared from hollow, octahedral Cu2 O supported palladium nanoparticles through a facile galvanic replacement reaction and carboxylic multi‐walled carbon nanotubes for electrochemical detection of caffeic acid in red wine.